Symposium 1: Revisiting the E-Quality in Networked Learning Manifesto - Beaty, Liz; Cousin, Glynis; Hodgson, Vivien (Proceedings of the International Conference on Networked Learning, 2010)
The purpose of this paper is to re-introduce the E-quality in Networked Learning Manifesto that was presented at the Networked Learning 2002 conference by the E-Quality Network and to reflect on its current applicability and meaning for networked learning. The paper will focus specifically on two of the five themes of the Manifesto; the working definition of networked (e)-learning and the need for a networked (e) - learning policy. In the paper we argue that the time is right to simply use the term networked learning and drop the ‘e’ in networked e-learning. This is because we think it is more important to foreground connectivity as a specific and important pedagogical feature of networked learning. We claim that an updated definition of networked learning should not only refer to being a pedagogy based on connectivity and the co-production of knowledge but also one that aspires to support e-quality of opportunity and include reference to the importance of relational dialogue and critical reflexivity in all of this. Following on from the definition of networked learning we reaffirm the point made in the original Manifesto that policy for networked learning should be based on explicit educational values and research. And further, that it should be reiterated by reference to research findings. We identify a number of policy areas that have been identified as important to consider at both the Government and Institutional level. We then argue for policy, when introducing Networked Learning into the curriculum and institutional educational practice, to be informed by the educational values and theory underpinning networked learning and not to be developed in isolation to these. The paper concludes by asking people to respond and draw on their research to comment on and hopefully develop the E-Quality Networked Learning manifesto and draw out issues for networked learning for the coming years